Value of preoperative three-dimensional planning software (AI-HIP) in primary total hip arthroplasty: a retrospective study - Xuzhuang Ding (SAGE Publishing, 2021)
Objective We performed a retrospective study to compare the accuracy of preoperative planning using three-dimensional AI-HIP software and traditional two-dimensional manual templating to predict the size and position of prostheses. The purpose of this study was to evaluate the accuracy of AI-HIP in preoperative planning for primary total hip arthroplasty. Methods In total, 316 hips treated from April 2019 to June 2020 were retrospectively reviewed. A typical preoperative planning process for patients was implemented to compare the accuracy of the two preoperative planning methods with respect to prosthetic size and position. Intraclass correlation coefficients (ICCs) were used to evaluate the homogeneity between the actual prosthetic size and position and the preoperative planning method. Results When AI-HIP software and manual templating were used for preoperative planning, the stem agreement was 87.7% and 58.9%, respectively, and the cup agreement was 94.0% and 65.2%, respectively. The results showed that when AI-HIP software was used, an extremely high level of consistency (ICC > 0.95) was achieved for the femoral stem size, cup size, and femoral osteotomy level (ICC = 0.972, 0.962, and 0.961, respectively). Conclusion AI-HIP software showed excellent reliability for predicting the component size and implant position in primary total hip arthroplasty.